Colposcopy and contraception. Comparative study of patients colposcopic processes contraceptive treatments - Rivas Gonzáles, Mauro (2015)
Colposcopic changes the hormonal contraceptive or IUD treatment produce them. The study in 360 patients and control subjects hundred suggests that neither contraception produces structural changes in the cervical epithelium which suggest a carcinogenic effect.